2015
DOI: 10.1007/s11426-015-5408-8
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(III)-catalyzed [3+2] annulative coupling between oximes and electron-deficient alkynes

Abstract: Rhodium(III)-catalyzed coupling between ketoximes and alkynes via C-H activation and annulation typically followed the [4+2] selectivity to afford isoquinolines. By designing alkynes bearing a highly electron-withdrawing group and under substrate control, we have successfully switched the selectivity of the coupling between oximes and alkynes to the alternative [3+2] annulation, leading to the efficient synthesis of indenamines. This process features good regioselectivity for both substrates, high efficiency, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…164 Here the use of electron-deficient alkynes was crucial for achieving good yields, and reactions proceeded with high regioselectivity to give the regioisomer shown. A variety of substituents were also tolerated on the aryl ring of the O -methoxy oxime.…”
Section: Additions To C=c π-Bonds Followed By Cyclization Upon Pomentioning
confidence: 99%
“…164 Here the use of electron-deficient alkynes was crucial for achieving good yields, and reactions proceeded with high regioselectivity to give the regioisomer shown. A variety of substituents were also tolerated on the aryl ring of the O -methoxy oxime.…”
Section: Additions To C=c π-Bonds Followed By Cyclization Upon Pomentioning
confidence: 99%
“…(3)]. Around the same time, Li and co‐workers demonstrated that trifluoromethanesulfonyl alkynes could be applied in rhodium‐catalyzed [3+2] annulation with O ‐methyl oximes to afford amino indene products 229 [Eq. (4)].…”
Section: N‐substituted Quaternary Centersmentioning
confidence: 99%
“…[ 1,2 ] Rhodium‐catalyzed CH functionalization has become an effective method to synthesize these compounds. [ 3–5 ] To ensure high selectivity for the CH bond activation in these reactions, [ 6–11 ] the directing groups are accommodated widely. [ 12–14 ]…”
Section: Introductionmentioning
confidence: 99%